Pengembangan Komik Matematika Dwibahasa (Indonesia-Melayu) untuk Meningkatkan Minat Belajar Anak PMI di Malaysia - Nabilah, Jennie; Sutini (Jurnal Riset Pembelajaran Matematika, 2025)
This study aims to develop and evaluate bilingual (Indonesia-Malay) mathematics comics designed to increase the learning interest of Indonesia students in Malaysia. Using a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, this study involved 7 students from the Indonesian Community Centre (ICC) in Muar, Johor. The effectiveness of bilingual comics was evaluated through measuring students' interest before and after the intervention using a Likert scale questionnaire. The validity of the comic content was assessed using Aiken's V, then the results showed that all aspects of the comic (material, media, and language) had good validity with an Aiken's V value > 0.70. The data were analyzed for normality and homogeneity, followed by a paired t-test to compare the pre test and post-test scores. The results showed that the use of bilingual comics significantly increased students' interest in learning, with a t-statistical value of 5.227, p = 0.002, and Cohen's d of -1.976, indicating a large measure of effect. These findings show that bilingual math comics can increase students' interest in learning mathematics.